2011
DOI: 10.3390/brainsci2010001
|View full text |Cite
|
Sign up to set email alerts
|

Why the Brain Knows More than We Do: Non-Conscious Representations and Their Role in the Construction of Conscious Experience

Abstract: Scientific studies have shown that non-conscious stimuli and representations influence information processing during conscious experience. In the light of such evidence, questions about potential functional links between non-conscious brain representations and conscious experience arise. This article discusses neural model capable of explaining how statistical learning mechanisms in dedicated resonant circuits could generate specific temporal activity traces of non-conscious representations in the brain. How r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 99 publications
(128 reference statements)
1
17
0
Order By: Relevance
“…Recent research is beginning to illuminate what is taking place. According to Dresp-Langley (2012) and referring mainly to neuro-psychological investigations, ''… a large number of studies have shown that non-conscious brain processes influence perceptions and representations embedded in ongoing conscious experience'' (p. 2). She argues, therefore, that far more is ''known'' than our deliberative, mindful and immediate thinking would suggest.…”
Section: Neuroscience and Recent Ideas In Cognitionmentioning
confidence: 99%
“…Recent research is beginning to illuminate what is taking place. According to Dresp-Langley (2012) and referring mainly to neuro-psychological investigations, ''… a large number of studies have shown that non-conscious brain processes influence perceptions and representations embedded in ongoing conscious experience'' (p. 2). She argues, therefore, that far more is ''known'' than our deliberative, mindful and immediate thinking would suggest.…”
Section: Neuroscience and Recent Ideas In Cognitionmentioning
confidence: 99%
“…Our results will be of great interest to those involved in the application of biological and neurological structures to the computational domain [20,21]. The codification of non-conscious reasoning has many potential applications in artificial intelligence and complex systems, which are an increasingly ubiquitous component of modern life.…”
Section: Discussionmentioning
confidence: 83%
“…The interactions between unconscious and conscious mental events were argued to be important by Freud [27], and this opinion is supported by recent neuroscientific study [28]. As only significant events within NARS enter the system's (conscious) experience, the same conclusion holds for NARS.…”
Section: Properties Of Narsmentioning
confidence: 82%